Rice Production in Vietnam: Characteristics and Application of Chitosan - Toan, Nguyen Van; Hanh, Tran Thi (Cutting Edge Research in Biology Vol. 2, 2022)
This work determines the suitable process for preparing chitosan solution, and focuses on its applications in rice production, in particular with respect to its activity in self-defense system of plants and growth promoter to increase rice production. Preparing chitosan solutions from shrimp shells for rice production was investigated. The chitosan produced from shrimp shells using dilute acetic acid proved effective in controlling plants infection by microbial agents leading to higher yields. The field data of our studies showed that the yields of rice significantly increased (~31%) after applying chitosan solution. In general, applying chitosan increased rice production and reduced cost of production significantly. Chitosan and chitosan solutions prepared by the proposed methods are more environmentally friendly, at low cost and can be applied at a large scale for mass production of rice and possibly for other agricultural plants.